In vitro Antifungal Susceptibility Profiles of Cryptococcus neoformans var. grubii and Cryptococcus gattii Clinical Isolates in Guangxi, Southern China - Al-Odaini, Najwa; Li, Xiu-ying; Li, Bing-kun; Chen, Xing-chun; Huang, Chun-yang; Lv, Chun-ying; Pan, Kai-su; Zheng, Dong-yan; Zheng, Yan-qing; Liao, Wan-qing; Cao, Cun-wei (Frontiers in Microbiology, 2021)
This study analyzed the in vitro drug sensitivity of Cryptococcus spp. from Guangxi, Southern China. 103 strains of Cryptococcus were recovered from 86 patients, 14 were HIV-positive and 72 were HIV-negative; 92 strains were identified as C. neoformans var. grubii, while 11 strains were identified as Cryptococcus gattii (5 C. gattii sensu stricto and 6 C. deuterogattii). The recovered strains were tested against commonly used antifungal drugs (fluconazole, amphotericin B, 5-fluorocytosine, itraconazole, voriconazole), and to novel antifungal drugs (posaconazole, isavuconazole) using CLSI M27- A4 method. The results showed all isolates were susceptible to most antifungal drugs, of which the MIC ranges were: fluconazole 0.05∼4 µg/mL, amphotericin B 0.25∼1 µg/mL, 5-fluorocytosine 0.0625∼2 µg/mL, itraconazole 0.0625∼0.25 µg/mL, voriconazole 0.0078∼0.25 µg/mL, posaconazole 0.0313∼0.5 µg/mL, isavuconazole 0.0020∼0.125 µg/mL C. neoformans var. grubii isolates, and 1~16 μg/mL for fluconazole, 0.0625~1 μg/mL for 5-fluorocytosine, 0.25~1 μg/mL for amphotericin B, 0.0625~0.25 μg/mL for itraconazole, 0.0156~0.125 μg/mL for voriconazole, 0.0156~0.25 μg/mL for posaconazole, and 0.0078~0.125 μg/mL for isavuconazole for C. gattii isolates. Furthermore, some C. neoformans var. grubii isolates were found to be susceptible-dose dependent to 5-fluorocytosine and itraconazole. Also, a reduction in the potency of fluconazole against C. gattii is possible. We observed no statistical differences in susceptibility of C. neoformans var. grubii and C. gattii in the tested strains. Continuous observation of antifungal susceptibility of Cryptococcus isolates is recommended to monitor the emergence of resistant strains.